1999
DOI: 10.1023/a:1018821718340
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study demonstrates overlapping substrate specificity between LNAA carrier and di/tripeptide transporter (hPEPT1) for PD 158473, an amino acid analog. Establishing Structure Transport Relationship (STR) for this overlap will aid in a design strategy for increasing oral absorption or targeting specific drugs to selected tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…PEPT1 has broad substrate specificity and is expressed in the GI tract [25,26]. This transporter can transport dipeptides, tripeptides, amino acid monoester prodrugs and β-lactam antibiotics [11,27,28,29,30,31,32,33]. Yang and coworkers demonstrated that the importance of PEPT1 transporter for the oral absorption of valacyclovir in PEPT1 knockout mice [34].…”
Section: Introductionmentioning
confidence: 99%
“…PEPT1 has broad substrate specificity and is expressed in the GI tract [25,26]. This transporter can transport dipeptides, tripeptides, amino acid monoester prodrugs and β-lactam antibiotics [11,27,28,29,30,31,32,33]. Yang and coworkers demonstrated that the importance of PEPT1 transporter for the oral absorption of valacyclovir in PEPT1 knockout mice [34].…”
Section: Introductionmentioning
confidence: 99%
“…Various dipeptides and peptidomimetics have been tested to characterize the hPEPT1 transporter and improve its affinity, 6,1719,22,3537 and mono amino acid ester prodrugs have been evaluated as hPEPT1 substrates. 3,13,14 Based on those reports, six amino acids were chosen to be N-terminal amino acids of the dipeptide.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid ester prodrugs of floxuridine and the antiviral agent acyclovir have been shown to be substrates of the PEPT1 transporter [ 14 , 15 ]. PEPT1 has broad substrate specificity for dipeptides, tripeptides, and β-lactam antibiotics [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Improved oral bioavailability of the valyl ester prodrug of acyclovir has been attributed to the presence of oligopeptide transporters [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%